Design and Analysis of the Driving Mechanism of Multi-DOF Flapping Wing Aircrafts - wang Wang; Xiaoxu Pang (Jixie chuandong)
In order to improve the flight performance of flapping wing aircrafts，a multi-DOF flapping wing mechanism based on space four-bar mechanism is designed by referring to the flight motion characteristics of small and medium-sized birds. Firstly，a kinematic model of the flapping wing driving mechanism is established through kinematic analysis. Then，a simulation model of the flapping wing mechanism is established in Adams to verify the theoretical analysis. The results show that， the design of a driving mechanism with single degree-of-freedom drive can realize the flutter，torsion，deflection multi-degree-of-freedom coupling movement，and the upper flutter limit is 34.65°，the lower flutter limit is -29.66°，the maximum torsion angle is 15.05°，the minimum torsion angle is -14.9°，the deflection angle range is -5.01°~5.21°； the track wich an "8" word output is the same as that of flying wing tips of small and medium-sized birds，which shows a good aerodynamic performance. The kinematic parameters obtained by simulation are in agreement with the theoretical calculation，which verifies the correctness of the theoretical calculation.